Lime Creek : fiction - Henry, Joe (Random House, 2011)
Working long and unforgiving hours on their blizzard-stricken Wyoming range, Spencer Davis and his sons, Luke and Whitney, oversee the life cycles of their horses until headstrong Luke falls in love and begins to assert his independence.